Retours sur les nationalismes sexuels - Alexandre Jaunait (Genre, Sexualité et Société)
This paper develops a critical analysis of the international conference entitled “Sexual Nationalisms. Gender, Sexuality, and the Politics of Belonging in the New Europe” that took place in Amsterdam, on January 27 and 28, 2011. This academic event intended to evaluate one of the most fruitful contemporary questions of gender studies, intertwining issues of sex and sexuality with the policies of national identity. The conference also gave birth to a fierce debate that casts light on the power issues which shape the academic field. In this review, I will analyse the different scientific issues at stake, and the ways in which they got entangled in two very different criticisms. This combination of critique and criticism illustrates the way gender and sexuality studies are permanently influenced by the political controversies that run through social movements and logics of mobilization.